Pengaruh Pengetahuan Keselamatan dan Kesehatan Kerja (K3) terhadap Perilaku Siswa Sesuai K3 pada Pratikum Instalasi Penerangan Listrik - Pradana, Yudi Putra; Taali, Taali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to determine the effect of K3 knowledge on K3 behavior of class XI TITL students of SMKN 3 OKU. This study was conducted on 34 students by giving posttest questions about K3 knowledge and using an assessment rubric filled in by the researcher. This study is a study that uses a quantitative approach with a descriptive method. Meanwhile, the type of research used is correlational research because it identifies how a variable affects another variable. Based on these results, it can be seen that a student's understanding of theory is very necessary. Theory is one of the most basic things that must be understood by students before carrying out practice. Theory as a starting point for practice is seen as knowledge about something. The importance of K3 knowledge for students is seen from various aspects. First, understanding K3 provides a strong foundation for students to recognize the risks they face. Second, routine training can make students ready to face work conditions. Third, applying K3 in learning creates a collective basis between students.